STATUS GIZI DAN HUBUNGANNYA DENGAN GANGGUAN MENSTRUASI PADA PETANI TEMBAKAU DI DESA AMBULU, KECAMATAN AMBULU, JEMBER - Indriyanti Indriyanti (UNUSA Press, 2019)
Menstrual disorders can be a sign of an illness or an abnormal hormonal system. The presence of hormonal abnormalities in a woman's body can be caused due to nutritional status. The purpose of this study was to analyze the relationship between nutritional status and menstrual disorders in tobacco farmers in Ambulu Village. The population in this study were female workers on tobacco farming in Ambulu village, Ambulu Subdistrict, Jember Regency with 39 workers. The number of research samples is taken from the entire population. The dependent variable in this study is nutritional status, and the independent variables are menstrual disorders. Based on research, it can be concluded that there is a relationship between nutritional status and menstrual disorders. as many as 26 people (66.7%). From the assessment of nutritional status, the results of the majority of respondents with abnormal nutritional status, both underweight and overweight, were as many as 20 people (51.2%). From the results of the statistical test, the value of the contingency coefficient is 0.436. It was concluded that the strong relationship between nutritional status and menstrual disorders in tobacco farmers in Ambulu Village, Jember Regency was included in the moderate level.